Estimating costs of hospitalizations associated with opioid use disorder or opioid misuse at a large, urban safety-net hospital—Denver, Colorado, 2017. (1st January 2021) - Arifkhanova, Aziza; McCormick Kraus, Emily; Al-Tayyib, Alia; Taub, Julie; Encinias, Annette; McEwen, Dean; Davidson, Arthur; Shlay, Judith C.
Highlights: Expanding inclusion criteria increased identified hospitalizations by 235 %. Of the 739 opioid-related hospitalizations in 2017, 75 % were billed to Medicaid. Using only diagnosis codes resulted in 519 missed opioid-related hospitalizations. Expanded inclusion criteria increased the accuracy of total cost estimates. Monitoring hospitalization trends and costs can guide future resource allocation. Abstract: Introduction: The national and state economic burden of the opioid crisis is substantial. This study estimated the number of hospitalizations associated with opioid use disorder (OUD) or opioid misuse (OM) and the cost of those hospitalizations at Denver Health (DH) Medical Center, a large, urban safety-net hospital. Methods: For 2017, direct inpatient medical costs for hospitalizations associated with OUD or OM at DH Medical Center were estimated and categorized by group and insurance type. Data were from the DH electronic health records database that included charge data. Hospitalizations associated with OUD or OM were identified using diagnostic codes and an expanded set of inclusion criteria including diagnostic codes, opioid withdrawal assessments, opioid-related admission notes, and medication prescriptions to treat OUD. Costs were estimated using cost-to-charge ratios specific to DH. Results: During 2017, 220 hospitalizations, $9, 834, 979 in total charges, $3, 690, 724 in estimated total costs, and $2, 115, 990 in total reimbursements were identified using diagnostic codes. Using the most expansive set of inclusion criteria, 739 hospitalizations, $35, 033, 157 in total charges, $13, 346, 099 in estimated total costs, and $7, 020, 877 in total reimbursements were identified. Of the 739 hospitalizations, Medicaid covered 546 hospitalizations (74 %), the largest proportion of total reimbursement (65 %), with estimated total costs of $10, 135, 048 (77 %). Conclusions: Our study identified considerable costs for hospitalizations associated with OUD or OM for DH. Estimating costs for hospitalizations associated with OUD or OM through use of expanded inclusion methodology can guide future program planning to allocate resources efficiently for hospitals such as DH Medical Center.